The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1128/aac.00899-07
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of Human Immunodeficiency Virus Type 1 in Medium by Copper Oxide-Containing Filters

Abstract: Human immunodeficiency virus type 1 (HIV-1) can be transmitted through breast-feeding and through contaminated blood donations. Copper has potent biocidal properties and has been found to inactivate HIV-1 infectivity. The objective of this study was to determine the capacity of copper-based filters to inactivate HIV-1 in culture media. Medium spiked with high titers of HIV-1 was exposed to copper oxide powder or copper oxide-impregnated fibers or passed through copper-based filters, and the infectious viral ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 46 publications
1
62
0
2
Order By: Relevance
“…Tested in simulated breathing conditions (28Á3 l min À1 ), no infectious viral particle was recovered from the copper oxide containing masks after 30 min, unlike with the control masks. In the same way, Borkow et al (2008) demonstrated the effectiveness of copper during HIV-1 passage through filters containing copper oxide powder or copper oxide-impregnated fibres (Borkow et al 2008). HIV-1 is inactivated when exposed to copper oxide in a dose-dependent manner, without neither cytotoxicity nor strain specificity.…”
Section: Copper As An Antiviral Surface Agentmentioning
confidence: 88%
See 1 more Smart Citation
“…Tested in simulated breathing conditions (28Á3 l min À1 ), no infectious viral particle was recovered from the copper oxide containing masks after 30 min, unlike with the control masks. In the same way, Borkow et al (2008) demonstrated the effectiveness of copper during HIV-1 passage through filters containing copper oxide powder or copper oxide-impregnated fibres (Borkow et al 2008). HIV-1 is inactivated when exposed to copper oxide in a dose-dependent manner, without neither cytotoxicity nor strain specificity.…”
Section: Copper As An Antiviral Surface Agentmentioning
confidence: 88%
“…() demonstrated the effectiveness of copper during HIV‐1 passage through filters containing copper oxide powder or copper oxide‐impregnated fibres (Borkow et al . ). HIV‐1 is inactivated when exposed to copper oxide in a dose‐dependent manner, without neither cytotoxicity nor strain specificity.…”
Section: Antiviral Activity Of Coppermentioning
confidence: 99%
“…Many sterilization and filtration processes have been devised that can effectively remove or reduce HIV viral infectivity (268273). Unfortunately, most of these technologies require tools not commonly available in households in developing countries or are prohibitively expensive.…”
Section: Interventionsmentioning
confidence: 99%
“…La elaboración de filtros con óxido de cobre ha permitido eliminar en forma eficiente el riesgo de transmisión de VIH a través de fluidos 14 . Los mecanismos involucrados en la actividad antiviral son la inactivación de una enzima proteasa importante para la replicación viral y daño a nivel de la envoltura fosfolipídica [14][15][16] .…”
Section: Actividad Antiviral Del Cobreunclassified